Assessment design, learning strategies and obstacles in facing Computer-Based Madrasah Exam on the English subject - Bahrun Bahrun; Rizki Maulana; Asnawi Muslem; Yulianti Yulianti (Studies in English Language and Education, 2023)
The objectives of this study were to describe how teachers design the Computer-Based Madrasah Exam (CBME) questions for English subjects, to investigate learning strategies students use, and to explore the obstacles the students face in this exam. Questionnaires and interviews were used as the instruments to collect data for this study. A number of 95 ninth-grade students and two English teachers of Madrasah Tsanawiyah Negeri No. 1 (MTsN 1; this school level is equivalent to junior high schools) in South Aceh, Indonesia, participated in this study. The data were analyzed quantitatively and qualitatively using thematic analysis. The results revealed that in designing the assessment of CBME, the teachers used four strategies which were preparing for the change in the final exam model, selecting sources in designing the exam questions, preparing students to face the exam in the new model, and resolving obstacles in developing the exam questions. Meanwhile, the students used five strategies in facing the exam, they are managing time, motivating themselves, creating study groups, practicing, and strengthening basic abilities. Furthermore, the obstacles that the students faced in the exam are a lack of skill in using a computer for the exam, slow internet access, limited computer availability, limitation of vocabulary mastery, taking time to understand questions, and peers’ interventions. Thus, this study suggests that more training is still needed for teachers in designing the assessment model of CMBE and the school also need sufficient facilities before they enforce CMBE to their students.